Baryonic B Meson Decays - Xiaotao Huang; Yu-Kuo Hsiao; Jike Wang; Liang Sun (Advances in High Energy Physics)
We review the two- and three-body baryonic B decays with the dibaryon (BB′¯) as the final states. Accordingly, we summarize the experimental data of the branching fractions, angular asymmetries, and CP asymmetries. Using the W-boson annihilation (exchange) mechanism, the branching fractions of B⟶BB′¯ are shown to be interpretable. In the approach of perturbative QCD counting rules, we study the three-body decay channels. In particular, we review the CP asymmetries of B⟶BB′¯M, which are promising to be measured by the LHCb and Belle II experiments. Finally, we remark the theoretical challenges in interpreting BB−⟶pp¯ρ− and BB−⟶pp¯μ−ν¯μ.